Prognostic impact of advanced lung cancer inflammation index and tumor load index in esophageal squamous cell carcinoma after neoadjuvant immunochemotherapy - Huang, Yizhou; Chen, Maohui; Yang, Zhenyuan; Zhang, Yongcong; Lin, Chuanquan; Zhang, Shuliang; Zeng, Taidui; Yu, Jun; Chen, Chun; Zheng, Bin (Frontiers in Immunology, 2026)
BackgroundEsophageal squamous cell carcinoma (ESCC) carries a high risk of recurrence after neoadjuvant immunochemotherapy and surgery. Both host inflammatory–nutritional status and circulating tumor markers may jointly influence clinical outcomes. We evaluated the prognostic value of the Advanced Lung Cancer Inflammation Index (ALI) and a composite Tumor Load Index (TL) to refine risk stratification in this setting.MethodsWe retrospectively analyzed 460 consecutive ESCC patients who received 2–3 cycles of PD-1 inhibitor plus platinum/taxane-based chemotherapy followed by esophagectomy. ALI was calculated as BMI × albumin/NLR. TL was derived via LASSO Cox regression from pre-treatment SCC-Ag, CEA, and CA19-9. Optimal cutoffs were identified using maximally selected rank statistics (ALI: 31.22; TL: 0.224). Patients were categorized as low-risk (high ALI/low TL), intermediate-risk (high ALI/high TL or low ALI/low TL), and high-risk (low ALI/high TL). Endpoints included overall survival (OS), disease-free survival (DFS), pathologic complete response (pCR), and major pathologic response (MPR).ResultsWith a median follow-up of 42 months, 3-year OS rates were 84.7%, 66.0%, and 34.6% for the low-, intermediate-, and high-risk groups, respectively (log-rank P < 0.001). Corresponding 3-year DFS rates were 75.4%, 61.6%, and 29.0%. In multivariable Cox models, intermediate- and high-risk groups had progressively worse OS (adjusted HR = 2.11 and 3.43) and DFS (adjusted HR = 1.64 and 2.62) compared with the low-risk reference (all P < 0.01). High-risk status independently predicted lower odds of achieving MPR (adjusted OR = 0.34, P = 0.002) and pCR (OR = 0.07, P = 0.011). A prognostic nomogram integrating risk group, ASA score, MPR, and ypN status showed strong discrimination (C-index = 0.742) and favorable calibration for 2-, 3-, and 4-year OS, with time-dependent AUCs of 0.759, 0.789, and 0.712.ConclusionsPre-treatment ALI and TL jointly provide robust and complementary prognostic information in ESCC patients receiving neoadjuvant immunochemotherapy. Low ALI combined with high TL identifies a biologically aggressive subset with poor pathologic response and inferior survival. Integration of ALI and TL may facilitate risk-adapted perioperative strategies and personalized treatment optimization.